Role of Alfuzosin in Ureteral Stent Related Urinary Symptoms Score: A Comparative Study - Shrestha, Santosh; Adhikari, DB; Gurung, A; Pradhan, S; Gurung, NV; Acharya, A; Shrestha, D; Poudel, SR; Chapagain, A; Shrestha, D; Lamichhane, P (Journal of Gandaki Medical College-Nepal, 2017)
Background: Ureteral stent placement is a routine urological procedure. However, patients inserted with ureteral stent exhibited increased urinary symptoms that compromise patients’ quality of life. Objective: To assess the efficacy of alpha blockers (Alfuzosin) in the management of ureteral stent related urinary symptoms. Methods: Total of 60 patients after ureteral stent insertion was randomly divided into two equal groups; 30 in alfuzosin group and the remaining 30 in control group. Urinary symptoms questionnaire was filled after two weeks and results were statistically analyzed. Results: Urinary symptoms like urgency, frequency and flank pain were significantly less in the alfuzosin group when compared with control group. Conclusion: Alpha blocker (Alfuzosin) was found to be effective in reducing ureteral stent related urinary symptoms. Journal of Gandaki Medical College Vol. 10, No. 1, 2017, page: 28-30